Cellulose conversion under heterogeneous catalysis - Dhepe, Paresh Laxmikant; Fukuoka, Atsushi (ChemSusChem, 2008)
In view of current problems such as global warming, high oil prices, food crisis, stricter environmental laws, and other geopolitical scenarios surrounding the use of fossil feedstocks and edible resources, the efficient conversion of cellulose, a non-food biomass, into energy, fuels, and chemicals has received much attention. The application of heterogeneous catalysis could allow researchers to develop environmentally benign processes that lead to selective formation of value-added products from cellulose under relatively mild conditions. This Minireview gives insight into the importance of biomass utilization, the current status of cellulose conversion, and further transformation of the primary products obtained
Keywords: Biomass; cellulose; heterogeneous catalysis; supported catalysts

Ce-Ni mixed oxide as efficient catalyst for H-2 production and nanofibrous carbon material from ethanol in the presence of water - Fang, Wenhao; Pirez, Cyril; Capron, Mickael; Paul, Sebastien; Raja, Thirumalaiswamy; Dhepe, Paresh Laxmikant; Dumeignil, Franck; Jalowiecki-Duhamel, Louise (RSC Advances, 2012)
Hydrogen production from ethanol steam reforming (H2O/C2H5OH = 3) was studied over Ce-Ni based catalysts issued from different preparation methods (co-precipitation (CP), impregnation (IMP) and incipient wetness impregnation (IWI)). Catalysts prepared by the CP method exhibit higher activity and much better stability compared to the other two types of catalysts. The Ni1CeOY-CP catalyst is able to completely convert ethanol at 450 degrees C to H-2, CO2 and CH4 (almost no CO is observed), with a H-2 yield of 3 moles of hydrogen produced per mole of ethanol converted. A very high H-2 yield of 4.6 mol mol(EtOH)(-1) is achieved over the Ni1CeOY-CP mixed oxide at 650 degrees C. Correlations between the preparation method, catalytic activity and stability, and type of carbon deposition are discussed. The CP method forms very active small sized NiO (15 nm) and CeO2 (4 nm) nanoparticles, leading to the formation of a lower amount of carbon deposition in the form of nanofibrous carbon materials, the size of which depends on the Ni related nanoparticles. For CP catalysts, the graphitic filaments obtained correspond to carbon nanofibers (CNFs) and carbon nanotubes (CNTs) with a much smaller and homogenous size compared to the filamentous carbon formed over the catalysts issued from the other preparation methods, in relation to the active particles size. The catalytic stability is attributed to the type of carbon formed.

Conversion of hemicellulose using acidic ionic liquids - Dhepe, Paresh Laxmikant; Matsagar, Babasaheb Mansub (WO2015111086 A1, 2014)
The present invention discloses one pot process for the conversion of hemicellulose into C5 sugars using ionic liquids in water media.

Conversion of biomass into sugars - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant; Dmitry, Murzin; Olga, Simakova (Biomass sugars for non-fuel applications, 2015)

Conversion of concentrated sugar solutions into 5-hydroxymethyl furfural and furfural using Bronsted acidic ionic liquids - Matsagar, Babasaheb M.; Munshi, Mudassir K.; Kelkar, Ashutosh A.; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2015)
Catalytic amounts of recyclable Bronsted acidic ionic liquids (BAILs) yielded HMF (73%) and furfural (81%) with high selectivity from highly concentrated solutions of D-fructose (40 wt%) and D-xylose (3 wt%), respectively. With a 6 wt% D-xylose solution, 73% yield was observed. An activity-property correlation of BAIL is established.